Optimization of management of origin of extraordinary situations risks during transportations of oil products by a railway transport - Бойченко, С.В.; Зеленько, Ю.В. (Proceedings of National Aviation University (archive), 2010)
Possibility of management of origin of extraordinary situations risks is considered at transportation of oil products by a railway transport. Intercommunication of functional strategy of providing of accident-freeness of vehicular process is resulted with other strategies.